2020
DOI: 10.1088/1361-6641/ab6ac1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deposition temperature on amorphous Ga2O3 solar-blind ultraviolet photodetector

Abstract: Solar-blind ultraviolet photodetectors have potential applications in space communication, ozone hole monitoring and missile tracking. Amorphous Ga 2 O 3 (a-Ga 2 O 3 ) films are deposited by a simple radio frequency magnetron sputtering at different deposition temperatures. Fully transparent devices on a quartz substrate are fabricated with high responsivity, wide detection range and good repeatability. With the increase of Ga 2 O 3 deposited temperature, the concentration of oxygen vacancy increases according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Our previous work illustrates that the recombination of electrons and holes leads to the fast process, while the slow-response component is from the carrier trapping/releasing at the Ga 2 O 3 /Ni interface. [31] Above experiment results indicate that the Ga 2 O 3 -based photodetector realized the fast and broadband UV light detection. Figure 2a shows the test diagram of Ni/p-NiO/n-ZnO/Ni memristor, and the positive current direction is from p-NiO to n-ZnO side in the following electrical measurements.…”
Section: Resultsmentioning
confidence: 76%
“…Our previous work illustrates that the recombination of electrons and holes leads to the fast process, while the slow-response component is from the carrier trapping/releasing at the Ga 2 O 3 /Ni interface. [31] Above experiment results indicate that the Ga 2 O 3 -based photodetector realized the fast and broadband UV light detection. Figure 2a shows the test diagram of Ni/p-NiO/n-ZnO/Ni memristor, and the positive current direction is from p-NiO to n-ZnO side in the following electrical measurements.…”
Section: Resultsmentioning
confidence: 76%
“…[ 36 ] Zhu et al demonstrated solar‐blind UV PDs based on a‐GaO x thin films prepared at different T s (RT‐500 °C) and found that photodetectors using the 500 °C deposited thin films possessed the best performance. [ 40 ] Battu et al also found that gallium oxide films deposited at T s = RT‐400 °C were amorphous and the amorphous‐to‐crystalline transformation occurred at T s = 500 °C. [ 54 ] All of the aforementioned results indicate that T s can greatly affect not only the material properties but also the device performance.…”
Section: Preparation Methods Of A‐gaoxmentioning
confidence: 99%
“…The substrate temperature during sputtering is gradually increased from room temperature to 700 • C. As shown in XRD patterns in Fig. 4, when the substrate temperature was at 400 • C and below, the resulting Ga 2 O 3 films behave as amorphous, while they stabilize as β -phase nanocrystals after that the substrate temperature reaches 500 • C. Zhu et al [36] investigated the effect of deposition temperature during magnetron sputtering on the performance of a-Ga 2 O 3 films and photodetectors, concluding that as the deposition temperature increases, roughness of the film decreases and thickness increases; meanwhile, the concentration of oxygen vacancy in a-Ga 2 O 3 increases correspondingly, which results in a higher responsivity.…”
Section: Magnetron Sputteringmentioning
confidence: 99%